Factors influencing utilization of municipal solid waste compost among urban farmers in western Uganda - Juliet Kiiza Kabasiita; Geoffrey Maxwell Malinga; Julius C. W. Odongo; Emmanuel Opolot (CABI Agriculture and Bioscience)
Abstract Background Effective management of solid waste is one of the most serious environmental problems confronting urban governments in developing countries due to insufficient financial resources and institutional capacity to provide basic solid waste management infrastructure, impoverished urban populations, low rates and coverage of collection, and rising food consumption rates. Composting has been touted as the most economical solution for reducing organic fraction of urban waste volumes while releasing vital nutrients for the soils. However, there is a paucity of information on utilization and associated factors of urban wastes in Uganda. This study aims to assess the level of utilization of Municipal Solid Waste (MSW) compost produced from Clean Development Mechanism (CDM) plants and associated factors among farmers in Fort Portal and Mbarara Municipalities, western Uganda. Methods Data was collected using a cross-sectional survey from 359 and 361 randomly selected farmers in Mbarara and Fort Portal, respectively. A semi-structured questionnaire was employed to collect quantitative data and analyzed statistically using SPSS and STATA statistical programs. Probit model was used to determine factors that influence farmers’ decisions to utilize MSW compost as a soil conditioner. Results The findings revealed a very low level of utilization in both municipalities, 1.7% in Fort Portal and 2.2% in Mbarara. The results indicated that annual farm income, access to other soil conditioners, experience with the use of fertilizers, membership to a farmers’ group and the cost of MSW compost significantly influenced farmers’ decision to use MSW compost. Conclusions The findings call for government investment in policies aimed at increasing the level of utilization of the MSW compost by improving accessibility to soil conditioners, creating opportunities for maximizing household incomes, farmer-to-farmer experience sharing, dissemination of information through extension programmes and other innovative communication approaches, operationalization of farmers’ groups and introduction of subsidy schemes on the price of compost through operational tax waivers in urban areas of Uganda. Finally, to guarantee quality and to improve the adoption of compost generated at the CDM plants, there is a need for research to assess the quality of MSW compost, undertake a supply chain analysis and cost–benefit study and set a price commensurate with the quality, and develop guidelines and rates of application of the MSW compost.